Continuous Human activity recognition using pure Recurrent Neural Network (RNN) architecture and IOT - Yadav, Dhirendra Kumar; Yadav, Hari Narayan Ray (Mid-West University Journal of Engineering & Innovation, 2025)
Applications like smart homes, security surveillance, healthcare, and workplace safety now depend heavily on Human Activity Recognition (HAR) and monitoring. Automated systems can respond quickly, stop dangerous situations, and provide individualized services when they can precisely identify and categorize human activity. The intricate temporal dependencies present in human motion are frequently difficult to capture by conventional HAR techniques that rely on hand-crafted features and shallow learning models [1]. This paper investigates the effectiveness of a pure Recurrent Neural Network (RNN) architecture for activity recognition using smartphone sensor data, despite the fact that deep learning models like CNNs and LSTMs have dominated recent HAR research. Without the need for manually created features, we suggest a simplified RNN-based framework that can identify temporal dependencies in unprocessed accelerometer and gyroscope data. Pure RNNs can attain competitive accuracy, as shown by experiments on the UCI HAR and WISDM datasets, which yielded results of 92.4% and 90.7%, respectively. The results imply that, when properly optimized, RNNs despite their simplicity remain feasible for HAR tasks.